Prediksi Kebangkrutan Menggunakan Model Grover, Zmijewski, & Altman Pada LPD di Kabupaten Gianyar Tahun 2013-2017 - Dewi, Ida Ayu Pradnyandhari; Ramantha, I Wayan (E-Jurnal Akuntansi, 2019)
LPDs throughout the Gianyar Regency have assets of Rp. 3.6 trillion, but from 2013 to 2017 there were 41 non-operating. This study uses other alternatives besides CAMEL and determines which model has the accuracy between the grover, zmijewski and altman models in predicting LPD bankruptcy. The results showed that in 2013, 2014, and 2016 there were 2 LPDs and in 2015 and 2017 there were 1 LPDs that were predictet bankrupt using the grover model. In 2013 there were 78 LPDs, in 2014 and 2017 there were 76 LPDs and in 2016 there were 77 LPDs that were predicted bankrupt using the zmijewski model. In 2013-2017 there were not LPDs that were predicted bankrupt using the altman model. The most accurate model that can be used in predicting bankruptcy by comparing management ratings on CAMEL is the altman model with an average percentage accuracy of 91.87%. Keywords: Bankruptcy; Grover Model; Zmijewski Model; Altman Model.